2022
DOI: 10.3390/ijms232113371
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Semi-Empirical Quantum Chemistry Methods on Soot Formation Simulation

Abstract: Soot molecules are hazardous compounds threatening human health. Computational chemistry provides efficient tools for studying them. However, accurate quantum chemistry calculation is costly for the simulation of large-size soot molecules and high-throughput calculations. Semi-empirical (SE) quantum chemistry methods are optional choices for balancing computational costs. In this work, we validated the performances of several widely used SE methods in the description of soot formation. Our benchmark study focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…It is now well established that theoretical methods are an efficient multipurpose tool for chemistry, biochemistry, and material science. Recent scientific efforts have shown that they can help us understand various phenomena, for example, reaction mechanisms or reactivity [ 35 , 36 , 37 , 38 ], electron density distribution [ 39 , 40 , 41 ], and elusive structure of complex biochemical systems or radical centers [ 42 , 43 , 44 ], anticancer [ 35 , 45 ] and antioxidant properties [ 46 , 47 , 48 , 49 , 50 , 51 ], soot formation [ 52 ] or pesticide decomposition [ 53 ]. The exchange coupling between paramagnetic centers has been a subject of such investigations at the density functional theory (DFT) and ab initio levels, but these studies were mainly limited to the interaction between metallic centers [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that theoretical methods are an efficient multipurpose tool for chemistry, biochemistry, and material science. Recent scientific efforts have shown that they can help us understand various phenomena, for example, reaction mechanisms or reactivity [ 35 , 36 , 37 , 38 ], electron density distribution [ 39 , 40 , 41 ], and elusive structure of complex biochemical systems or radical centers [ 42 , 43 , 44 ], anticancer [ 35 , 45 ] and antioxidant properties [ 46 , 47 , 48 , 49 , 50 , 51 ], soot formation [ 52 ] or pesticide decomposition [ 53 ]. The exchange coupling between paramagnetic centers has been a subject of such investigations at the density functional theory (DFT) and ab initio levels, but these studies were mainly limited to the interaction between metallic centers [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%